STUDY OF ADHERENCE TO DRUG THERAPY OF PATIENTS WITH CARDIOVASCULAR DISEASES IN DISTRICT HOSPITAL OF SMALL TOWN IN SARATOV REGION AND IN CARDIOLOGY DEPARTMENT OF UNIVERSITY CLINIC IN SARATOV - Yu. V. Bulaeva; E. A. Naumova; O. N. Semenova (Столичная издательская компания, 2018)
Aim. To study the relation of various factors with adherence to long-term drug therapy in patients with cardiovascular diseases in district hospital of small town in Saratov Region and patients from clinical hospital of Saratov medical university.Material and methods. The hospitalized patients with cardiovascular diseases were included into the prospective study of long-term adherence to treatment. Questioning of patients with the determination of the attitude of respondents to their health, the desire to receive information about the disease, the level of awareness of the therapy, the degree of participation in the treatment process, the nature of the relationship with the attending physician was performed. A year after discharge, control calls were made to patients to learn whether the patient was continuing treatment prescribed a year ago in the hospital. The data on patient adherence in both hospitals were analyzed.Results. 108 patients in the district hospital (58% of selected patients) and 70 in the Saratov hospital (33% of selected patients) responded to all questions in the questionnaire during hospitalization. Successful reaching by phone 12 months after discharge from the hospital took place in 74 patients of the small town and 40 patients of the regional center. The continuation of treatment was found in 28 (38%) and 24 (50%) patients, respectively. Patients who continued treatment significantly differed from those, who stopped therapy, by presence of myocardial infarction in anamnesis [14 (78%) patients in the university hospital and 6 (60%) patients in the district hospital; p<0.01] as well as acute cerebrovascular accident [6 (78%) patients in the university hospital and 4 (75%) patients in the district hospital; p<0.05] and stable angina class I-III [22 (61%) patients in Saratov and 28 (44%) patients in the small town; p<0.01]. Adherence to recommendations after 12 months was found in patients who considered that doctor or relatives were responsible for their health (6 patients in Saratov and 12 - in the small town; p<0.05) and believed that attending physician determines the portion of information provided to the patient [20 (60%) patients of the district hospital and 11 (63%) patients in the university clinic; p<0.05 for university clinic].Conclusion. The adherence to long-term treatment after discharge remained low and did not exceed 50% among patients in both groups. The paternalistic model continued to dominate in the doctor-patient interconnection system.